The impact of new information regime on the Jakarta stock exchange. - Nelmida, .; Md. Nassir, Annuar; Hassan, Taufiq (EuroJournals Publishing, Inc., 2009)
Stock market efficiency is an important concept, especially in understanding the working of the stock markets particularly in emerging stock market such as Indonesia. The efficiency of the emerging markets assumes greater importance as the trend of investments is accelerating in these markets as a result of regulatory reforms and removal of other barriers for international equity investments. This study provides empirical evidence on the impact of new information regime on the efficiency of the Jakarta Stock Exchange by using weak-form efficiency test. This study uses data from the returns series of the Composite Index and selected individual companies before regulation changes from 1991 to 1995 and after regulation changes from 1996 to 2004. This paper employs the BDS test, which is widely used to distinguish random independent and identically distributed error terms. Three variants of BDS were performed to evaluate weak-form efficiency namely: (i) the normalized BDS test, (ii) the BDS test under ARMA and (iii) the BDS test under EGARCH. The findings indicate that in general and with exceptions the null hypothesis of independent and identically distributed (iid) error term is not rejected and insignificant at the 5% level on the Composite Index and individual companies before and after regulation changes and more prominent after the imposition of the new information regime. The results suggest that it is difficult to reject the random walk hypotheses for most of the return series after the regulatory reform. This result confirms that the market is weak-form efficient, except for daily and weekly returns before regulation changes and except for daily return after regulation changes. The results also implied that the new information regime have impacted on the Jakarta Stock Exchange by making it becoming more efficient.